Soft reliability: An interdisciplinary approach with a user-system focus - Koca, Aylin; Funk, Mathias; Karapanos, Evangelos; Rozinat, Anne; Van Der Aalst, Wil M.P.; Corporaal, Henk; Martens, Jean Bernard O.S.; Van Der Putten, Piet H.A.; Weijters, A. J.M.M.(Ton); Brombacher, Aarnout Cornelis (My University, 2009)
A recent trend in technological innovation is towards the development of increasingly multifunctional and complex products to be used within rich socio-cultural contexts such as the high-end office, the digital home, and professional or personal healthcare. One important consequence of the development of strongly innovative products is a growing market uncertainty regarding 'if', 'how', and 'when' users can and will adopt such products. Often, it is not even clear to what extent these products are understood and interacted with in the intended manner. The mentioned problems have already become an evident concern in the field, where there is a significant rise in the numbers of seemingly sound products being complained about, signaling a lack of soft reliability. In this paper, we position soft reliability as a growing and critical industrial problem, whose solution requires new academic expertise from various disciplines. We illustrate potential root causes for soft reliability problems, such as discrepancy between the perceptions of users and designers. We discuss the necessary approach to effectively capture subjective feedback data from actual users, e.g. when they contact call centers. Furthermore, we present a novel observation and analysis approach that enables insight into actual product usage, and outline opportunities for combining such objective data with the subjective feedback provided by users.
Keywords: Business process design; Customer-perceived quality; Information flow analysis; New product development; Process mining; Soft reliability